Islamic design : a genius for geometry - Sutton, Daud. (New York : Walker and Company, 2007)
Throughout their long history the craft traditions of the Islamic world evolved a multitude of styles applied to a great variety of media but always with unifying factors that make them instantly recognisable. Harmony is central. There are two key aspects to the visual structure of Islamic design, caligraphy using Arabic script - one of the world's great calligraphic traditions - and abstract ornamentation using a varied but remarkably integrated visual language. This art of pure ornament revolves around two central themes; crystalline geometric patterns, the harmonic and symmetric al subdivision of the plane giving rise to intricately interwoven designs that speak of infinity and the omnipresent center, and idealised plant form, spiraling tendrils, leaves, buds and flowers embodying organic life and rhythm.
Decorative arts and crafts.
Design.
Islam.
Keywords: Design; Islamic art; Islamic art and symbolism; Symbolism in art